Factors contributing to negative emotional experiences in intercultural academic communication - Hermanto (Faculty of Communications Science, Dr. Soetomo University, 2025)
This study investigates the factors contributing to students’ negative emotional experiences during communication with peers, faculty members, and staff in the culturally diverse setting of Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia. Employing a mixed-methods approach, the research examined the interplay of communication styles, interpersonal relationships, and socio-cultural differences of 126 respondents. Results indicate that a significant majority, 75.4% of students, reported experiencing negative emotions during campus communication, with female students reporting a higher prevalence within their gender group. Qualitative analysis identified three primary categories of contributing factors: ‘tone and style of communication,’ ‘interpersonal relationships,’ and ‘social and cultural differences’ along with their sub-categories, such as impolite or disrespectful language and feelings of being undervalued or unsupported, primarily stemming from communication styles and interpersonal relationships emerged as the most significant contributors to negative emotional experiences. The study highlights the critical role of communicative styles and interpersonal dynamics in eliciting negative emotions within a diverse university environment. These findings underscore the need for fostering inclusive and supportive communication practices to mitigate emotional strain and enhance student well-being and academic achievement.